The quality of life of patients with ovarian cancer as an indicator of functional assessing the effectiveness of anticancer therapy - Kolesnik, O. O.; Rybin, A. I. (Journal of Education, Health and Sport, 2017)
The aim of this study was to evaluate quality of life in patients with platinumresistant ovarian cancer, depending on the pharmacoresistance and differentiated use of chemotherapy. It is shown that the output value by the subscales of the questionnaires EORTC QLQ-C30 and FACT-G in patients assigned to different clinical groups were comparable. When using a differentiated approach in the treatment of patients with ovarian cancer significantly improved performance on physical scales (PF), role (RF) and emotional functioning (EF). In addition, patients from III and IV groups had decreased intensity of nausea (NV) and general weakness (FA). With differentiated application of chemotherapeutic agents with metabolic support total score by FACT-G questionnaire was in Group III 77,8±0,9 points, and in the IV group - 77,9±0,8 points, which was significantly higher than obtained in the first and group II - 72,2±1,2 and 71,6±0,9 points. Described differences were held during all follow-up observation.